Dynamic Cache Replacement Strategy of Space Information Network Based on Cache Value. Issue 1 (1st June 2022) - Cai, Rui-yan; Qian, Yang; Wei, De-bin
Abstract: With the development of space network communication technology, satellite cache becomes possible. However, due to the limited space on the satellites, content replacement has become a major factor affecting network performance. Aiming at the limited cache resources of space network nodes and the low cache hit rate of nodes, a space information network dynamic cache replacement strategy (SINDR) based on cache value is proposed. On the basis of considering the popularity of the content and the cost of caching, the strategy also calculates the caching value of the content by quantifying the entropy increase of the node, and assigns a reasonable weight to each factor according to the Analytic Hierarchy Process. The cache value function is reconstructed; finally, the content of the virtual node and the physical satellite node that will serve the area is replaced by combining the characteristics of the space network, so as to obtain the optimal utilization of satellite cache resources. The simulation results show that, compared with the existing cache replacement strategies, the cache replacement strategy proposed in this paper can effectively improve the average cache hit rate and reduce the average user acquisition delay in the space information network environment.